(untitled) (Al-Aasar, 2025)
Karen Armstrong, a prominent scholar, approaches religion through a universalist lens, emphasizing shared spiritual experiences across traditions, while Islamic Sufi doctrines are deeply rooted in Islamic theology and practices. This comparative analysis examines the differences between Armstrong’s views and Sufi teachings, highlighting their distinct perspectives on God, religious boundaries, and spiritual practices. Armstrong views God as a concept limited by human understanding, advocating a flexible, universal spirituality that transcends specific religious frameworks. In contrast, Sufis perceive God as the all-encompassing source of existence, emphasizing divine unity (wahdat al-wujud) and direct communion through love and annihilation of the self (fana). While Armstrong sees Sufism as a universal spiritual phenomenon, Sufis anchor their philosophy in Islamic principles, balancing esoteric experiences with adherence to Sharia. Armstrong’s focus on religion as a force for social harmony and ethical progress contrasts with the Sufi emphasis on personal spiritual transformation and divine proximity. Additionally, Sufi practices like ecstatic worship (zikr, dance) differ from Armstrong’s more intellectual and historical approach to spirituality. These differences reflect their distinct contexts: Armstrong’s modern, global perspective versus the Sufis’ traditional Islamic framework. Despite shared themes of compassion and spirituality, their approaches diverge in their foundational premises and practical expressions, offering unique insights into the nature of religious experience and its role in human life.